TRANSFORMASI PERAN PEREMPUAN MUSLIM DALAM ERA SOCIETY 5.0 : Perspektif Teologis Dan Sosiologis - Lina Nur Anisa, Lina Nur Anisa (Institut Agama Islam Negeri Ponorogo, 2024)
This article aims to discuss the transformation of the roles of Muslim women in the era of Society 5.0 from theological and sociological perspectives. This study employs a qualitative approach using library research. The data collection technique used is documentation, with data analysis techniques including content analysis, induction, and deduction. The conclusions of this article are as follows. First, from a theological perspective, Islamic teachings inherently support gender equality and justice. Inclusive and progressive interpretations of religious texts can encourage positive social change and empower women. The Qur'an and Hadith offer a framework that supports the active role of women in society, both in domestic and public spheres. Second, the sociological perspective provides an understanding of the social and cultural dynamics that influence women's roles. Globalization and social media have shaped the identity of Muslim women and accelerated social change. Through social media platforms, Muslim women can express themselves, share experiences, and build supportive communities, enabling them to challenge stereotypes and prejudices that often hinder social progress.